Analisis Kesulitan Guru Sekolah Dasar dalam Pembelajaran Matematika di SDN 012 Kp. Panjang Airtiris - Adityawarman Hidayat; Zulhendri Zulhendri; Bunga Casandra (Journal on Education, 2021)
The difficulty of elementary school math teachers in math learning is that teachers are difficult at planning the mathematical learnig process, teachers are difficult at carrying out the mathematical learning process and teachers are difficult at communicating with students during math study. The purpose of this study is to know the extent of the planning of mathematics learning teachers have done, the performance of mathematics learning by teachers as well as the communication process between teachers and the student in the math class. The type of research used is qualitative descriptive analysis of data and information obtained from research for later interpretation according to the fact that in planning the learning process, the most frequent difficulty is determining the learning media by as much as (25%) and then creating teaching methods (18,75%). The next challenge to the mathematical learning process, the most frequent difficulty is to motivate students to ask the question of a magnitude (44,44%). The last difficulty is in communicating with the students. The most frequent challenge is to stimulate a students interest in math lessons by ( 42,85%). Should a math teacher have special skills in order to increase the students interest in math and not impress the monotonous in the matter of speaking.